(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
The analysis developed experimental designs of solar collectors and calculations of its heat balance, the efficiency, the main components of the energy loss to the environment and their relationship on the basis of a series of studies installing in the summer in the normal operating mode and stagnation. Keywords:solar collector, helioplant, solar battery.